Semiotic Analysis of Gender Equality Representation in Soy Sauce Product Advertising - Dian Nurvita Sari; Leila Mona Ganiem (Nyimak: Journal of Communication, 2021)
Gender equality and inequality is an important issue in society and the nation. In a patriarchal culture such as in Indonesia, in the domestic sphere, the role of women tends to be more dominant. This social construction is usually reinforced by the mass media. but in a soy sauce product advertisement, the issue of gender equality is shown by placing the role of women in the domestic and public spheres. The purpose of the study was to reveal the meaning behind the symbols representing gender equality between the roles of men and women in domestic life contained in the true husband version of the ABC soy sauce advertisement. The research method uses Roland Barthes’ semiotic approach through analysis of two levels of marking, namely denotation, and connotation, then proceeds to uncover hidden myths. The results of this study indicate that the burden of the dual role of working mothers in a patriarchal culture fosters the myth that women are creatures who have superpowers capable of working in the public sphere without leaving their work in the domestic sphere, the myth of a true husband, namely a husband who can share roles to do the work. domestic work and the myth of space genderization. In the ABC version of the true husband soy sauce advertisement, gender equality is achieved by cooperation between husband and wife regardless of work and space-based on gender.Keywords: Representation of gender equality, semiotic analysis, soy sauce product advertisement ABSTRAKKesetaraan dan ketidaksetaraan gender adalah isu penting dalam masyarakat dan bangsa. Dalam budaya patriarki seperti di Indonesia, di ranah domestic, peran perempuan cenderung lebih dominan. Konstruksi social tersebut biasanya diperkuat oleh media massa. namun dalam suatu iklan produk kecap, isu kesetaraan gender  ditampilkan dengan menempatkan peran perempuan di ranah domestic dan public. Tujuan penelitian adalah untuk mengungkap makna dibalik simbol-simbol representasi kesetaraan gender antara peran laki-laki dan perempuan dalam kehidupan rumah tangga yang terkandung dalam iklan kecap ABC versi suami sejati. Metode penelitian menggunakan pendekatan semiotika Roland Barthes melalui analisis dua tingkat penandaan,  yaitu denotasi dan konotasi lalu dilanjutkan dengan membongkar mitos yang tersembunyi.  Hasil penelitian ini menunjukan bahwa beban peran ganda yang dimiliki oleh ibu pekerja dalam budaya patriarki menumbuhkan mitos bahwa perempuan adalah makhluk yang memiliki kekuatan super mampu bekerja di ranah publik tanpa meninggalkan pekerjaannya di ranah domestik, mitos suami sejati yakni seorang suami yang mampu berbagi peran untuk mengerjakan pekerjaan domestik rumah tangga dan mitos genderisasi ruang. Dalam iklan kecap ABC versi suami sejati kesetaraan gender tercapai dengan adanya kerjasama antara suami dan istri tanpa memandang pekerjaan dan ruang berdasarkan gender.Kata Kunci: Analisis semiotik, representasi kesetaraan gender, iklan produk kecap